Restoring strong cosmic censorship in Reissner–Nordström–de Sitter black holes via non-minimal electromagnetic-scalar couplings - Jie Jiang; Jia Tan (European Physical Journal C: Particles and Fields, 2023)
Abstract We investigate whether the Strong Cosmic Censorship (SCC) Conjecture can be reinstated at the classical level in Reissner–Nordström–de Sitter (RNdS) black holes by introducing non-minimal couplings between the electromagnetic and scalar fields in Einstein–Maxwell-scalar (EMS) theory. By conducting numerical calculations, we find that the SCC can be restored within a specific range of the coupling constant. Notably, for a given value of the cosmological constant, there exists a critical coupling constant above which the EMS theory satisfies the SCC. These findings suggest that the non-minimal couplings between the electromagnetic and scalar fields may play a crucial role in the restoration of the SCC in RNdS spacetime. Additionally, under negative coupling constants, the low-lying modes of nearly extremal black holes exhibit $$β > 1,$$ β > 1 , enabling $$C^2$$ C 2 extensions beyond the Cauchy horizon and intensifying the violation of the SCC.